Community justice centres mainstreamed? Making the impossible possible - Murray, Sarah (Contemporary justice review, 2024)
Community Justice Centres (CJC) are a burgeoning justice phenomenon which focus on local justice solutions and which house a court with wrap-around community supports to address the underlying causes of offending. Drawing on case studies of CJCs in the USA and New Zealand, this article explores what justice systems can draw from this innovative court model by trying to mainstream its benefits. It argues that mainstreaming CJC initiatives holds real promise provided that investment is made in planning model design and leadership and in forging meaningful and sustainable partnerships with the community and key stakeholders. While there are risks that too much of the model will get lost in seeking to centralise it, it can also open up access to place-based solution-focused approaches to more citizens. It argues that the key is retaining the importance of ‘the local’ as the heartbeat of the CJC paradigm.